-x+1/3y=14/3
-(-x+1/3y)=-(14/3)
x-1/3y=-14/3
x=1/3y-14/3
x=(y-14)/3
-2x-1/3y=13/3
-1/3y=2x+13/3
3*(-1/3y)=3*(2x+13/3)
-y=6x+39/3
-y=6x+13
-(-y)=-(6x+13)
y=-6x-13
If you want to find x and y it is:
y=-6[(y-14)/3]-13
y=[(-6y+504)/3]-13
y=[3(-2y+168)/3]-13
y=(-2y+168)-13
y=-2y+168-13
y=-2y+155
y+2y=155
3y=155
y=155/3
x=(y-14)/3
x=[(155/3)-14]/3
x=[(155/3)-(42/3)]/3
x=(113/3)/3
x=113/(3*3)
x=113/9
2007-01-11 01:07:25
·
answer #1
·
answered by Bill 1
·
0⤊
0⤋
First you can find x right off the bat by using systems of equations. You add both equations show the 1/3y cross out each other. Then you would have two equations. One would be
-x=14/3 and the other equation being -2x=13/3.This is not what I expected, but assuming you know algebra these X values do not have the same value. Therfore the answer is No Solutions.
2007-01-11 00:14:13
·
answer #2
·
answered by Anonymous
·
0⤊
1⤋
add x to both sides in equation 1:
1/3y=14/3+x
subtract 14/3 from both sides of equation 1:
x=1/3y-14/3
put into equation 2:
-2(1/3y-14/3)-1/3y=13/3
distribute:
-2/3y+28/3-1/3y=13/3
combine like terms:
-y+28/3=13/3
subtract 28/3 from both sides:
-y=-15/3
cancel negatives and reduce fraction:
y=5
put y=5 into equation 1 to get x:
x=1/3(5)-14/3
distribute:
x=5/3-14/3
subract and reduce:
x=-9/3=-3
soooo.....y=5, x=-3
you can double check by putting numbers into both equations
2007-01-11 02:21:13
·
answer #3
·
answered by persnickety118 1
·
0⤊
0⤋
Add both the equations .....
U will get -3x = 27/3......
Now solving x= 27/-9 or x = -3
Putting value of x in equation 1,u get
-(-3) + 1/3y = 14/3
now 1/3y = 5/3
therefore y = 5
x = -3 y=5
2007-01-11 00:14:16
·
answer #4
·
answered by KP-Rox 2
·
0⤊
0⤋
-x + 1/3y = 14/3 .............1)
-2x - 1/3y = 13/3 .............2)
Once you notice +1/3y in eqn 1) and -1/3y in eqn 2), add
1) and 2) to get the ff:
-3x = 14/3 + 13/3 = 27/3 = 9
x = - 9/3 = -3
Substitute this value for x in 1) to get
3 + 1/3y = 14/3
1/3y = 14/3 - 3 = (14-9)/3 = 5/3
y = 5/3 *3 = 5
2007-01-11 00:13:59
·
answer #5
·
answered by Paleologus 3
·
0⤊
0⤋
Assuming it is a 'minus' sign before x and 2x in both the equations:
Adding both equations,
- x + 1/3y = 14/3
-2x - 1/3y = 13/3
-----------------------------
-3x = 27/3 (y term is cancelled as the sum of the y terms is zero)
-x = 3
So, x = -3 and y = 0.
If it is not a minus sign before the x terms in the two equations,
value of x = 3; y = 0
2007-01-11 00:09:00
·
answer #6
·
answered by jobless 4
·
0⤊
1⤋
-x+(1/3)y=14/3 ----(1)
-2x-(1/3)y=13/3 ----(2)
(1) + (2) : -x-2x+(1/3)y-(1/3)y=14/3+13/3
i.e.-3x = 27/3
x=-3
Substitute this value in one of the above equations, then we can find the value of y.
Substitute x=-3 in equation (1) we get,
3+(1/3)y=14/3
(1/3)y=14/3-3
(1/3)y=5/3
i.e. y=5
There for the solution for the above equations is x=-3, y=5.
2007-01-11 00:24:44
·
answer #7
·
answered by hirunisha 2
·
0⤊
0⤋
simple!
-x + 1/3y = 14/3
-2x- 1/3y = 13/3
adding,
-3x = 27/3
-3x = 9
x=-3
so, y=5
2007-01-11 01:02:58
·
answer #8
·
answered by sushobhan 6
·
0⤊
0⤋
first we multiply two of the equation by 3
then multiply (1) by 2
then (1) - (2) to eliminate x
3y=15
Y=3
substite it into one of the equation
-x+1/3(3)=14/3
-x+1=14/3
-x=11/3
x=-11/3
2007-01-11 00:48:33
·
answer #9
·
answered by kevin 1
·
0⤊
1⤋
go solve it yourself
2007-01-11 00:08:28
·
answer #10
·
answered by just me 3
·
0⤊
0⤋